Analysis of Conflicting Regulations concerning the Food Estate Program and Customary Land in Accordance to Indonesian Customary Law Principles - Guslandi, Ariel (West Science Law and Human Rights, 2023)
As a rechstaat, Indonesia has human rights and a law protection guarantee that is regulated in the Constitution of the Republic of Indonesia (UUD 1945). To ensure the protection of the law and human rights, it is necessary to have a legal basis that regulates these matters, including customary rights. The regulations of customary rights are regulated in Article 18B paragraph 2 of the UUD 1945, Law Number 5 of 1960 concerning the Basic Regulation of Agrarian Principles, Law Number 39 of 2014 concerning Plantation, and Law Number 6 of 2023 concerning Job Creation. However, there is a problem in the social field, as happened in Central Kalimantan Province that customary land was turned into a 600-hectare cassava plantation food estate program without involving Dayak indigenous people from planning to implementation. Moreover, Dayak indigenous people do not get any benefits from the food estate program. These reasons are that there are a few legal problems that contradict the food estate program and customary rights.